2018
DOI: 10.1016/j.chiabu.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Peer teasing experiences of fathers and their children: Intergenerational associations and transmission mechanisms

Abstract: Being the victim or perpetrator of peer teasing threatens children’s immediate and long-term well-being. Given that many individual and contextual risk factors for peer victimization are transmitted within families, we tested whether fathers’ childhood victimization experiences were directly or indirectly (via poor parenting and poor child adjustment) associated with their children’s increased risk for similar experiences. Generation two (G2) fathers (n = 130) who had been assessed since age 9 years participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 60 publications
0
8
1
1
Order By: Relevance
“…Preliminary validity information for this single-item measure of peer victimization comes from two studies. The first study reported that the teacher-report version of this item was significantly moderately correlated with maternal and paternal reports of a two-item victimization scale (Kerr, Gini, Own, & Capaldi, 2018). The second found that when children reported being teased in an autism diagnostic interview, 88.9% of parents also indicated that their child was victimized with the CBCL peer victimization item (Nowell, Brewton, & Goin-Kochel, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Preliminary validity information for this single-item measure of peer victimization comes from two studies. The first study reported that the teacher-report version of this item was significantly moderately correlated with maternal and paternal reports of a two-item victimization scale (Kerr, Gini, Own, & Capaldi, 2018). The second found that when children reported being teased in an autism diagnostic interview, 88.9% of parents also indicated that their child was victimized with the CBCL peer victimization item (Nowell, Brewton, & Goin-Kochel, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…We averaged the T1 and T2 indicators of risk taking and inhibitory control because (1) all of these indicators were significantly correlated over time; (2) this approach maximizes the available longitudinal data within a parsimonious model; and (3) combining scores across multiple assessments provides more reliable estimates of population–level data. This approach has been widely used in longitudinal studies (e.g., Haraden et al, 2017; Kerr et al, 2018). The significance of the hypothesized mediating path was examined using the bias-corrected bootstrap method based on 5000 samples (Mackinnon et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the peer aggression and transmission literature are two rather distinct fields with not very much overlap, which probably also contributes to a lack of recent studies on this topic. In fact, to the knowledge of the authors, only two studies have examined transmission of peer-related aggression but have used high-risk rather than population samples and arrived at different conclusions: Whereas fathers' peer bullying perpetration was transmitted to offspring (Farrington, 1993), no evidence was found for intergenerational transmission of fathers' peer teasing (Kerr et al, 2018). By studying this association in a population sample and not solely for fathers, the field gains a better understanding both of long-term correlates of peer aggression as well as on preconception predictors of behavioral development for offspring.…”
Section: Transmission Of Aggressive Behavior Across Generationsmentioning
confidence: 99%